Mechanical and degradation properties of advanced platelet-rich fibrin (A-PRF), concentrated growth factors (CGF), and platelet-poor plasma-derived fibrin (PPTF) - Kazushige Isobe; Taisuke Watanebe; Hideo Kawabata; Yutaka Kitamura; Toshimitsu Okudera; Hajime Okudera; Kohya Uematsu; Kazuhiro Okuda; Koh Nakata; Takaaki Tanaka; Tomoyuki Kawase (SpringerOpen, 2017)
Abstract Background Fibrin clot membranes prepared from advanced platelet-rich fibrin (A-PRF) or concentrated growth factors (CGF), despite their relatively rapid biodegradability, have been used as bioactive barrier membranes for alveolar bone tissue regeneration. As the membranes degrade, it is thought that the growth factors are gradually released. However, the mechanical and degradable properties of these membranes have not well been characterized. The purpose of this study was to mechanically and chemically characterize these membranes. Methods A-PRF and CGF clots were prepared from blood samples collected from non-smoking, healthy donors and were compressed to form 1-mm-thick membranes. Platelet-poor plasma-derived fibrin (PPTF) clots were prepared by adding bovine thrombin to platelet-poor plasma. A tensile test was performed at the speed of 1 mm/min. Morphology of the fibrin fibers was examined by SEM. A digestion test was performed in PBS containing trypsin and EDTA. Results In the tensile test, statistical difference was not observed in Young's modulus, strain at break, or maximum stress between A-PRF and CGF. In strain at break, PPTF was significantly weaker than CGF. Likewise, fibrin fiber thickness and crosslink density of PPTF were less than those of other membranes, and PPTF degraded faster than others. Conclusions Although the centrifugal conditions are different, A-PRF and CGF are prepared by essentially identical mechanisms. Therefore, it is conceivable that both membranes have similar mechanical and chemical properties. Only PPTF, which was prepared by a different mechanism, was characterized as mechanically weaker and enzymatically more degradable.